2016
DOI: 10.1186/s13039-016-0234-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative deletion mapping at 1p31.3-p32.2 implies NFIA responsible for intellectual disability coupled with macrocephaly and the presence of several other genes for syndromic intellectual disability

Abstract: BackgroundWhile chromosome 1 is the largest chromosome in the human genome, less than two dozen cases of interstitial microdeletions in the short arm have been documented. More than half of the 1p microdeletion cases were reported in the pre-microarray era and as a result, the proximal and distal boundaries containing the exact number of genes involved in the microdeletions have not been clearly defined.ResultsWe revisited a previous case of a 10-year old female patient with a 1p32.1p32.3 microdeletion display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Deletions in the 1p31.3 locus involving the NFIA gene have been reported several times in the literature (Campbell, Wang, & Hunter, ; Chen et al, ; Ji, Salamon, & Quintero‐Rivera, ; Koehler et al, ; Labonne et al, ; Lu et al, ). Recently, Labonne et al () used comparative deletion mapping and identified NFIA as a gene in the minimal region of overlap among reported 1p31.3‐p32.2 microdeletions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletions in the 1p31.3 locus involving the NFIA gene have been reported several times in the literature (Campbell, Wang, & Hunter, ; Chen et al, ; Ji, Salamon, & Quintero‐Rivera, ; Koehler et al, ; Labonne et al, ; Lu et al, ). Recently, Labonne et al () used comparative deletion mapping and identified NFIA as a gene in the minimal region of overlap among reported 1p31.3‐p32.2 microdeletions.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions in the 1p31.3 locus involving the NFIA gene have been reported several times in the literature (Campbell, Wang, & Hunter, ; Chen et al, ; Ji, Salamon, & Quintero‐Rivera, ; Koehler et al, ; Labonne et al, ; Lu et al, ). Recently, Labonne et al () used comparative deletion mapping and identified NFIA as a gene in the minimal region of overlap among reported 1p31.3‐p32.2 microdeletions. By comparing the phenotype of five individuals with NFIA alterations (including three microdeletions and two translocations that disrupted NFIA ) and supporting animal studies, Lu et al () suggested that NFIA gene haploinsufficiency was responsible for a novel syndrome that included central nervous syndrome malformations as well as ureteral and renal defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asterisks represent autosomal control probes. Sivasankaran et al, 1997;Zinner and Batanian 2003;Shaw-Smith et al, 2004;Gillberg and FitzPatrick, 2010;Chen et al, 2011;Ji et al, 2014;Tassano et al, 2015;Labonne et al, 2016]. There are also 5 cases with significantly smaller deletions, all presenting with a milder phenotype ( fig.…”
mentioning
confidence: 99%
“…With the exception of the 1p36 syndrome (MIM 607872), interstitial deletions affecting the short arm of chromosome 1 are rare, with only ∼ 20 cases reported in the literature [Labonne et al, 2016]. Three of these are deletions encompassing the whole 1p31.1p31.3 region ( fig.…”
mentioning
confidence: 99%